2002
DOI: 10.1254/jjp.88.270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Reactive Oxygen Species on the Guinea Pig Trachea and Its Epithelium

Abstract: ABSTRACT-Reactive oxygen species (ROS) are key factors playing important roles in tissue damage of airways under different pathological conditions. Effects of ROS (superoxide anion, H2O2 and hydroxyl radical) were recorded on isometric tension of intact and epithelium denuded, not precontracted guinea pig trachea. Superoxide anion was produced by xanthine /xanthine oxidase and hydroxyl radical either by FeSO4/H2O2 or FeSO4/ascorbic acid. In intact preparations, the muscle tension was unaffected by superoxide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Indeed, Mátyás et al (2002) showed that superoxide anion, hydroxyl radicals, and hydrogen peroxide cause the tracheal smooth muscle to contract, the latter being the ROS responsible for the greatest increase in muscle tone. In addition, the effects of these free radicals are contained by antioxidant defenses present in the intact epithelium, and epithelial damage potentiates the contractile effect of these ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Mátyás et al (2002) showed that superoxide anion, hydroxyl radicals, and hydrogen peroxide cause the tracheal smooth muscle to contract, the latter being the ROS responsible for the greatest increase in muscle tone. In addition, the effects of these free radicals are contained by antioxidant defenses present in the intact epithelium, and epithelial damage potentiates the contractile effect of these ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that excess ROS may sensitize C-fiber afferents, which in turn leads to the development of airway hypersensitivity (Tsai et al, 2006 , 2009 ; Shen et al, 2012 ; Ruan et al, 2014 ) and thus ROS are likely to be the major mediators responsible for the CIH-induced consequences observed in this study. Additionally, excessive ROS may promote the release of other mediators such as cyclooxygenase metabolites and ATP (Chakraborti et al, 1989 ; Matyas et al, 2002 ; Tsai et al, 2009 ) within the airways, many of which are also able to sensitize airway C-fiber afferents (Ho et al, 2000 ; Gu et al, 2003 ; Tsai et al, 2009 ). Capsaicin, adenosine, and α,β-methylene-ATP are agonists of TRPV1, adenosine A1, and P2X receptors, respectively, which are located at the terminals of the LVCFs (Lin et al, 2009 , 2013 ).…”
Section: Discussionmentioning
confidence: 99%